Lever arm dysfunction in cerebral palsy gait - Theologis, Tim (Springer Berlin Heidelberg, 2013)
Skeletal structures act as lever arms during walking. Muscle activity and the ground reaction against gravity exert forces on the skeleton, which generate torque (moments) around joints. These lead to the sequence of movements which form normal human gait. Skeletal deformities in cerebral palsy (CP) affect the function of bones as lever arms and compromise gait. Lever arm dysfunction should be carefully considered when contemplating treatment to improve gait in children with CP.